2015
DOI: 10.4172/2161-1017.1000202
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Peroxisome Proliferator-Activated Receptor-γ (PPARγ) Pro12Ala Polymorphism and Dietary Fat Intake among Turkish Patients with Metabolic Syndrome: A Cross Sectional Study

Abstract: Background: The metabolic syndrome is a complex disorder which occurs as a result of the interaction between genetic and environmental factors. The interaction between the peroxisome proliferator-activated receptor gamma (PPARγ) Pro12Ala polymorphism and dietary fats has been proposed to act in the pathogenesis of syndrome. This study aimed to verify whether dietary nutrient intake interacts with the PPARγ Pro12Ala polymorphism to modulate the features of the syndrome. Methods: A total of 150 patients with met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Previous research has also found different associations between dietary fatty acid intake and BMI, insulin sensitivity, risk of diabetes and lipid profile according to PPAR‐γ Pro12Ala genotype 79 . The first study to report a gene–diet interaction with PPAR‐γ Pro12Ala polymorphism suggested that Ala‐allele carriers who ingest SFAs are more susceptible to the metabolic syndrome than Pro homozygotes 80 . Some studies have also suggested an association between low dietary polyunsaturated fatty acids consumption and higher BMI in Ala‐allele carriers compared to Pro homozygotes, but, when the dietary ratio is high, the converse occurs: Ala‐allele carriers who consume SFAs are more prone to metabolic syndrome than Pro homozygotes 81,82 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also found different associations between dietary fatty acid intake and BMI, insulin sensitivity, risk of diabetes and lipid profile according to PPAR‐γ Pro12Ala genotype 79 . The first study to report a gene–diet interaction with PPAR‐γ Pro12Ala polymorphism suggested that Ala‐allele carriers who ingest SFAs are more susceptible to the metabolic syndrome than Pro homozygotes 80 . Some studies have also suggested an association between low dietary polyunsaturated fatty acids consumption and higher BMI in Ala‐allele carriers compared to Pro homozygotes, but, when the dietary ratio is high, the converse occurs: Ala‐allele carriers who consume SFAs are more prone to metabolic syndrome than Pro homozygotes 81,82 .…”
Section: Discussionmentioning
confidence: 99%
“…79 The first study to report a gene-diet interaction with PPAR-γ Pro12Ala polymorphism suggested that Ala-allele carriers who ingest SFAs are more susceptible to the metabolic syndrome than Pro homozygotes. 80 Some studies have also suggested an association between low dietary polyunsaturated fatty acids consumption and higher BMI in Ala-allele carriers compared to Pro homozygotes, but, when the dietary ratio is high, the converse occurs: Ala-allele carriers who consume SFAs are more prone to metabolic syndrome than Pro homozygotes. 81,82 It is unclear whether foods and/or these dietary patterns serve as PPAR ligands or whether they act directly in glucose metabolism pathways that are more evident when PPAR activity is low.…”
Section: Discussionmentioning
confidence: 99%